1985
DOI: 10.1016/s0750-7658(85)80185-4
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of histamine release by fatty acids. A new in vitro model investigating adverse drug reactions in various species

Abstract: : Histamine release caused by drugs and/or their solvents is a well known phenomenon. In this study, both in vivo (anaesthetized and conscious dogs) and in vitro (isolated rat peritoneal, human and guinea-pig lung mast cells) models were used. Cremophor E1 and six derivatives of 12-hydroxystearic acid were compared for their histamine releasing abilities. Although the three types of isolated mast cells responded similarly, histamine release being observed with DH (the diester of 12-hydroxystearic acid with pol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…[26]. In addition, the rat peritoneal mast cell has been found to be useful in the study of a number of agents producing histamine release in man [27,28], and may, therefore, accurately represent vancomycin effects induced clinically.…”
Section: Discussionmentioning
confidence: 99%
“…[26]. In addition, the rat peritoneal mast cell has been found to be useful in the study of a number of agents producing histamine release in man [27,28], and may, therefore, accurately represent vancomycin effects induced clinically.…”
Section: Discussionmentioning
confidence: 99%
“…The solubilizing agent for Saffan Ò was a polyethoxylated castor oil, Cremophor Ò -EL, which caused histamine release in animals by stimulating mast cell degranulation. This histamine released caused unacceptable adverse events (Clarke et al, 1975;Fisher, 1975;Dodman, 1980;Ennis & Lorenz, 1985). Because alfaxalone has a wide margin of safety, a formulation containing no Cremophor Ò -EL has been a target of research for some years (Brewster et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…1a,c, LORENZ et al 1976, 1977aLORENZ and DOENICKE, 1978a,b), patients (Figs. 1b,2b, LoRENZ et al 1976PHILBIN et al 1982a) and several animal species (LORENZ and DOENICKE 1978a;NEUGEBAUER and LORENZ 1981;Moss et al 1982) and isolated cells (ENNIS and Lorenz 1985a).…”
Section: Koch-dale Criteriamentioning
confidence: 99%
“…It is, however, not widely known that cyclosporin A is dissolved using cremophor El as a solubilizer. This mixture of fatty acids and its chemically modified derivatives (LORENZ et al 1982b) was demonstrated in a whole series of articles as a histamine releaser (LORENZ et al 1971a(LORENZ et al , 1977b(LORENZ et al , 1981a(LORENZ et al , 1982b and as a potentiator of histamine release responses (ENNIS and LORENZ 1985a. This may explain unexpected cardiovascular reactions and very high plasma histamine levels at certain times after transplantation (LORENZ and DOENICKE 1985a) Finally, histamine is involved in wound healing.…”
mentioning
confidence: 95%